Internet and health contents - Espanha, R. (2017)
Information and communication technologies provide autonomy possibilities to individuals, concerning their social and individual background, favouring a disposition to escape from traditional control, enabling them to face modern society’s contradictions, without forgetting the relevance of networks in constructing new social movements, possible only in a context of a broader use of information and communication technologies. Therefore, the question that is discussed in this paper is what is the meaning of daily information and communication practices to the health problem individual management? How ICT’s are shaped by individual needs and social contexts, namely in the case of health communication? Individual health and its daily management never involved as much information as nowadays. Great amounts of health and medicine information are available from several sources – whether professional health sources, different kinds of specialists, public and private institutions or patient and/or consumers groups – through a multiplicity of information channels, from media to local or interpersonal base, interacting with doctors and other health professionals, family, friends, work colleagues, etc. Closely connected to network societies problematic and a relevant health component in contemporary societies, is the issue of understanding how Internet and media in general contribute to subjects autonomy. In this paper we will focus on the questions related directly with the internet use for health purposes, in the Portuguese case.